Annexin I and dexamethasone effects on phospholipase and cyclooxygenase activity in human synoviocytes - Annaleise V. Sampey; Paul Hutchinson; Eric F. Morand (Mediators of Inflammation)
Annexin I is a glucocorticoid-induced mediator with anti-inflammatory activity in animal models of arthritis. We studied the effects of a bioactive annexin I peptide, ac 2–26, dexamethasone (DEX), and interleukin-1β (IL-1β) on phospholipase A2 (PLA2) and cyclooxygenase (COX) activities and prostaglandin E2 (PGE2) release in cultured human fibroblast-like synoviocytes (FLS). Annexin I binding sites on human osteoarthritic (OA) FLS were detected by ligand binding flow cytometry. PLA2 activity was measured using 3H-arachidonic acid release, PGE2 release and COX activity by ELISA, and COX2 content by flow cytometry. Annexin I binding sites were present on human OA FLS. Annexin I peptide ac 2–26 exerted a significant concentration-dependent inhibition of FLS constitutive PLA2 activity, which was reversed by IL-1β. In contrast, DEX inhibited IL-1β-induced PLA2 activity but not constitutive activity. DEX but not annexin I peptide inhibited IL-1β-induced PGE2 release. COX activity and COX2 expression were significantly increased by IL-1β. Annexin I peptide demonstrated no inhibition of constitutive or IL-1β-induced COX activity. DEX exerted a concentration-dependent inhibition of IL-1β-induced but not constitutive COX activity. Uncoupling of inhibition of PLA2 and COX by annexin I and DEX support the hypothesis that COX is rate-limiting for PGE2 synthesis in FLS. The effect of annexin I but not DEX on constitutive PLA2 activity suggests a glucocorticoid-independent role for annexin I in autoregulation of arachidonic acid production. The lack of effect of annexin I on cytokine-induced PGE2 production suggests PGE2-independent mechanisms for the anti-inflammatory effects of annexin I in vivo.